The effects of a green rooibos extract on the reproductive function of obesity-induced insulin resistant or hypertensive male wistar rats - Manirafasha, Claudine (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.